2022
DOI: 10.3389/fimmu.2022.889736
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Sustainable Platform for Preparation of a High-Quality Immunoglobulin G as an Urgent Treatment Option During Emerging Virus Outbreaks

Abstract: During the pre-vaccine era of the COVID-19 pandemic convalescent plasma has once again emerged as a major potential therapeutic form of passive immunization that in specific cases still represents irreplaceable treatment option. There is a growing concern that variable concentration of neutralizing antibodies, present in convalescent plasma which originates from different donors, apparently affects its effectiveness. The drawback can be overcome through the downstream process of immunoglobulin fraction purific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
2
0
1
Order By: Relevance
“…demonstrated that SARS-CoV-2-specific IgM antibodies significantly contribute to virus neutralization and are present in different quantities in sera of recovered persons. 29 Wei et al . 22 also confirmed that the lower antibody levels produced in natural infection resulted in greater protection at the given antibody level compared to vaccination, reviewing assumption that the level of protection is associated with the antibodies and is dependent on the mechanism (infection or vaccination) generating the antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that SARS-CoV-2-specific IgM antibodies significantly contribute to virus neutralization and are present in different quantities in sera of recovered persons. 29 Wei et al . 22 also confirmed that the lower antibody levels produced in natural infection resulted in greater protection at the given antibody level compared to vaccination, reviewing assumption that the level of protection is associated with the antibodies and is dependent on the mechanism (infection or vaccination) generating the antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Kurtović et al demonstrated that SARS-CoV-2-specific IgM antibodies significantly contribute to virus neutralization and are present in different quantities in sera of recovered persons. 22 Wei et al 21 also confirmed that the lower antibody levels produced in natural infection resulted in greater protection at the given antibody level compared to vaccination, reviewing assumption that the level of protection is associated with the antibodies and is dependent on the mechanism (infection or vaccination) generating the antibodies.…”
Section: Subsequent Immunization Of Convalescents By Vaccination Modu...mentioning
confidence: 93%
“…Aufgrund des hohen Aufwands für Technologie und Maßnahmen zur Virussicherheit gibt es in der Mehrzahl der Nicht-Industrieländer bis heute weder eine lokale Infrastruktur zum Sammeln von Blutplasma noch für die Fraktionierung. Um bei der Ausbreitung neuer Pathogene schnell mit der Herstellung von HIG-Produkten beginnen zu können, ist darum die Ausweitung des lokalen Blut-und Plasmaspendewesens und das Etablieren lokaler Aufreinigungsmöglichkeiten notwendig [81,82]. Um die möglichst effiziente Nutzung von Hyperimmunplasma sicherzustellen wird es nötig sein, wie bei den normalen Immunglobulinpräparaten, die technologischen Verbesserungen in den Herstellprozessen konsequent umzusetzen.…”
Section: Diskussionunclassified